Catastrophic caldera-forming eruptions and climate perturbations: the result of tectonic and magmatic controls on the Paleocene-Eocene Kilchrist Caldera, Isle of Skye, NW Scotland - Drake, Simon Murray; Brown, David; Beard, Andrew; Kumlertsakul, Padej; Thompson, David; Bays, Charlotte; Millar, Ian; Goodenough, Kathryn (Volcanica, 2022)
Caldera-forming eruptions are amongst the most hazardous events in the Earth’s history, and understanding their formation is essential to forecasting activity at active calderas worldwide. In this study we present new field and geochronological evidence for a Paleocene-Eocene caldera from Skye, NW Scotland. Magma exploited a regional thrust fault as a conduit, and then ponded against intrusive igneous rocks emplaced against a regional extensional fault. Replenishment of silicic magma reservoirs with basaltic magma triggered eruptions. The eruptions typically deposited extremely coarse ignimbrites, demonstrating catastrophic collapse of the caldera, which occurred via an inner ring fault and a complexly faulted marginal zone. Collapse was followed by remobilisation of silicic magma and caldera resurgence. The magma consumed dolostone country rocks, causing significant release of CO2 and contributed to the Paleocene-Eocene Thermal Maximum. Our results demonstrate how tectonics localise magma and caldera development, and how this can cause cataclysmic volcanic and climatic hazards.